Fatigue criterion improvement of Gough and Nishihara & Kawamoto to predict the fatigue damage of a wide range of metallic materials. (June 2017) - Khalij, Leila; Pagnacco, Emmanuel; Troian, Renata
Highlights: New fatigue criterion for a wide range of metallic materials. Extension of Gough and Nishihara & Kawamoto approaches. Equivalent shear stress amplitude obtained from a prismatic convex hull method. Improvement of fatigue damage assessment for brittle and extremely brittle materials. Abstract: An improved multiaxial high-cycle model based on the Gough and Nishihara & Kawamoto approaches is presented. The proposal is a compromise between the measure of the equivalent shear stress amplitude, obtained from a prismatic convex hull method, and the amplitude of the first stress invariant. This makes the criterion an effective approach to predict quickly the failure initiation for wide range of materials (from ductile metals to extremely brittle metals). The results obtained from our proposal are compared to experimental data reported in the literature.